Addition of Pineapple Hump Extract to Feed and Probiotics in Cultivation Media on the Performance of Catfish (Clarias gariepinus) - Kartina Kartina; Wahyu Afiansyah; Awaludin Awaludin (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2023)
Catfish is a consumption fish that is in great demand so that production continues to be increased. Pineapple hump are known to be rich in bromelain enzymes. The bromelain enzyme has properties similar to proteolytic enzymes, which have the ability to hydrolyze proteins. This study aims to determine the optimal dose of pineapple hump extract in feed on the growth performance of the Sangkuriang catfish. The test fish used were catfish seeds measuring 3-5 cm and weighing ± 3 g. This study used an experimental method in a completely randomized design (CRD) consisting of 4 treatments and 3 replications, with P0 (control) 0% pineapple hump extract; P1 dose 0.75%; P2 1.5% and P3 3% extract/kg feed. Probiotics were added to the rearing medium to maintain water quality as much as 1.5 ml/liter. The results showed that the addition of pineapple hump extract in the P2 treatment with a dose of 1.5% showed the highest value at absolute length of 4.4 cm, at absolute weight of 2.3 g, Specific Growth Rate (SGR) of 4.5% and the survival rate is 86% and the lowest value for each observation is in the P0 (control) treatment. However, the statistical test did not show a significant difference in results. Based on the results of the study, pineapple hump extract can be used in feed to increase the growth of the Sangkuriang catfish at a dose of 1.5%/kg of feed.